The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/slct.201701497
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Estimation of Molecules Incorporating Heavier Elements from van‐der‐Waals Corrected ECC‐DOSY

Abstract: Aggregate formation of organometallic compounds can be straightforwardly observed and interpreted through DOSY molecular weight (MW) estimation. Recently, the power‐law approach and preparation of external calibration curves (ECCs) has propelled the applicability of this DOSY MW estimation. However, effective prediction of MWs of molecules containing heavier elements (e. g. halogenated compounds) has not been sufficiently accounted for. Hence, we introduce specialized ECCs for various halogenated molecules. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…16 Since the latter are insoluble in our case, only monomeric and homochiral dimeric complexes (both consisting only of the major enantiomer) stay in solution. This was supported by 1 H DOSY NMR experiments [24][25][26][27] of enantiopure (-)-NBE reacted with ZnMe2 in toluene-d8, which indicated that the complexes have a higher molecular weight (MW) than expected from monomeric (-)-NBE-ZnMe over a broad temperature range (cf. Supplementary Fig.…”
Section: Discussionmentioning
confidence: 85%
“…16 Since the latter are insoluble in our case, only monomeric and homochiral dimeric complexes (both consisting only of the major enantiomer) stay in solution. This was supported by 1 H DOSY NMR experiments [24][25][26][27] of enantiopure (-)-NBE reacted with ZnMe2 in toluene-d8, which indicated that the complexes have a higher molecular weight (MW) than expected from monomeric (-)-NBE-ZnMe over a broad temperature range (cf. Supplementary Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Theeffect of ligand size on cluster size was investigated by DOSY NMR using the external calibration method described by Stalke and co-workers (see Supporting Information). [48] For 1-Ca and 1-Ba in benzene we found in both cases molecular weights lower than calculated for the monomers (1-Ca:c alc. 697, found 515; 1-Ba:c alc.7 95, found 548).…”
Section: Angewandte Chemiementioning
confidence: 56%
“…Chemical shifts were referenced to residual protic impurities in the solvent ( 1 H) or the deuterio solvent ( 13 C) and reported relative to external SiMe 4 ( 1 H, 13 C), H 3 PO 4 ( 31 P), Me 2 Se ( 77 Se), or Me 2 Te ( 125 Te). For molecular weight estimation, external calibration curves together with a correction factor dependent on the molar density were used in the CC-MW estimation software v1.3 [ 27 , 28 ]. APCI-DIP (atmospheric pressure chemical ionization-direct inlet probe) mass determinations were performed on a Finnigan LCQ Deca ( ThermoQuest ).…”
Section: Methodsmentioning
confidence: 99%